DETERMINANTS OF DOMESTIC PHYSICAL VIOLENCE AGAINST WOMEN IN TURKEY - Alkan, Ã–mer; Ãœnver, Åžeyda (Humanities & Social Sciences Reviews, 2021)
Purpose of the study: This study aims to determine the factors affecting the exposure of women in Turkey 15 years of age and older to physical violence by their husband/intimate partner. Methodology: In this study, the micro-data set of the "Research on Domestic Violence against Women in Turkey" conducted by Hacettepe University Institute of Population Studies in 2008 and 2014 was used. In this data set, the data of 18518 women aged 15 and over were used, 11722 in 2008 and 6796 in 2014. Factors affecting women’s physical violence were determined using binary logistic and probit regression analysis. This study focuses on the physical violence of the husband/partner, which is the most common type of domestic violence against women. Main Findings: The variables of survey year, region, education level, individual income, marital status, health status, the number of children, and being exposed to violence from first degree relatives are seen to be significant. According to the results obtained, the expected probability of exposure to physical violence women who were subjected to economic, verbal, and sexual violence by their husbands/intimate partners was more than 39.8%, 127.35%, and 83.68%, respectively. Applications of this study: The study outcome indicate that important steps to reduce domestic physical violence against women in Turkey should be taken. In order to prevent new cases of abuse, coordinated efforts to raise awareness of the problem of domestic physical violence against women will encourage action. Novelty/Originality of this study: In this study, factors affecting the exposure of women in Turkey, 15 years old and older, to physical violence by their husband/intimate partner were identified. In the study, the socio-demographic and economic characteristics of women and to what extent the various risk factors related to husband/intimate partners were critical for the women’s exposure to physical violence.